NON ENGLISH DEPARTMENT STUDENTS’ PERCEPTION ON THE USE OF INSTAGRAM IN SPEAKING ENGLISH - Setiawati; Yanti Anggraini; Ika Purnama Sari (J-Shelves of Indragiri (JSI), 2024)
Instagram is a mobile application designed to enhance the photo-sharing experience on social media platforms. Instagram is one of social media that had been used by educator in learning process. Instagram included elements that make it potentially useful for language learning activities, the platform has been used extensively in the educational sector. Therefore, this research attempted to explore the opinions of non-English department students on the usage of Instagram for speaking English. This research used quantitative method, and the research design was survey. The population used 82 respondents non major English Department of STAI Hubbulwathan Duri at the first semester, academic year 2023-2024. The respondents consist of Islamic education department, development of Islamic society department, and Syariah banking Department. The students have the same qualification and academic background before doing a survey. They had ever learned speaking English by using Instagram. The reseracher took all respondents as sample in this research because size of the population be fewer 100. The researcher used questionnaires for data collection techniques, speaking in class while gathering information. This research investigated non English department students’ perception on the use instagram in speaking English showed positive perception in using instagram in speaking English. The percentage of agree was 81,16%. It showed Students can practice in a different environment on Instagram, which boosts their confidence. Additionally, the students felt at ease utilizing Instagram as a forum for speaking English and less bothered by their mistakes. They also felt encouraged in speaking English.